HmuY proteins of the Porphyromonas genus show diversity in heme-binding properties - Śmiga, Michał; Olczak, Teresa (Frontiers in Cellular and Infection Microbiology, 2025)
IntroductionBacteria of the Porphyromonas genus, belonging to the Bacteroidota phylum, colonize various host niches in health and disease. As heme auxotrophs, they rely on heme uptake for iron and protoporphyrin IX. A key heme acquisition system in Porphyromonas gingivalis is the Hmu system, where the hemophore-like HmuYPg protein plays a major role. HmuYPg coordinates heme-iron using two histidines, whereas other known HmuY proteins produced by other Bacteroidota members prefer a pair of histidine-methionine or two methionines. Some of them bind heme via the protoporphyrin ring without heme-iron coordination, similar to the P. gingivalis HusA protein.MethodsThis study used bioinformatics, spectroscopic, and electrophoretic methods to compare the genomic organization of the Hmu system and the structural and functional properties of HmuY proteins within the Porphyromonas genus.Results and DiscussionWe revealed variations in the heme-binding properties of proteins belonging to the HmuY family and susceptibility to modifications in their heme-binding pockets. These findings suggest that HmuY proteins may have undergone evolutionary adaptations to enhance bacterial survival in the human microbiome, contributing to dysbiosis and disease development. These evolutionary changes may explain the superior heme-binding ability of P. gingivalis HmuYPg compared to HmuY homologs produced by other Porphyromonas species.